2010
DOI: 10.1007/s00441-010-1076-3
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+-binding protein calretinin is selectively enriched in a subpopulation of the epithelial rests of Malassez

Abstract: During tooth development, the inner and outer enamel epithelia fuse by mitotic activity to produce a bilayered epithelial sheath termed Hertwig's epithelial root sheath (HERS). The epithelial rests of Malassez (ERM) are the developmental residues of HERS and remain in the adult periodontal ligament (PDL). Although the cellular regulation of the Ca(2+)-binding proteins parvalbumin, calbindin-D28k, and calretinin has been reported in the inner and outer enamel epithelia during tooth development, an involvement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…In parallel, calbindin-D 28k was upregulated in the rests of Malassez of Msx2 +/mice and even more in Msx2 -/-. This pattern is not physiological (Korkmaz et al 2010), as confirmed here in Msx 2 +/+ control mice. The same observation was also repeated for amelogenin in the same pathophysiological context.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…In parallel, calbindin-D 28k was upregulated in the rests of Malassez of Msx2 +/mice and even more in Msx2 -/-. This pattern is not physiological (Korkmaz et al 2010), as confirmed here in Msx 2 +/+ control mice. The same observation was also repeated for amelogenin in the same pathophysiological context.…”
Section: Discussionsupporting
confidence: 68%
“…This study focused on calcium-binding proteins, as some of them are highly expressed in ameloblasts but not significantly expressed in the non-ameloblastic cells (Hotton et al 1995;Hubbard 1995;Berdal et al 1996;Korkmaz et al 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The features of shed teeth in CIPA patient suggest that NTRK1 could play an important role in root formation. Some studies have shown that TRKA is a convenient marker for identifying and characterizing Hertwig's root sheath and epithelial rests of Malasseze of the forming root [27], [28]. Moreover, NGF/TRKA expressed in human periodontal tissue may contribute to the regeneration and the innervation of periodontal tissue [29], [30].…”
Section: Discussionmentioning
confidence: 99%